Neurodevelopmental impact of mining-related contamination in children from the Sonora river basin - Mejía-Cruz, Diana; Ávila-Chauvet, Laurent; Robles-Morua, Agustín; Murataya-Gutierrez, Joselinn (Frontiers in Pediatrics, 2025)
IntroductionIn August 2014, the Buenavista del Cobre mine in northern Mexico released over 40,000 m3 of acidified copper sulfate into the Sonora River, causing long-term environmental contamination. Children in nearby communities face increased neurodevelopmental risks due to prolonged exposure to toxic metals such as lead and arsenic. This study examines cognitive and executive functioning outcomes in exposed children, considering the roles of nutrition, parenting practices, and prenatal biological risk factors.MethodsA cross-sectional study was conducted with 238 children aged 5–13 years: 215 from mining-impacted communities and 23 from the non-exposed control community of Álamos. Children completed selected BANETA neuropsychological subtests (e.g., attention, academic skills, motor coordination), while caregivers completed the BRIEF-P, Parenting Practices Inventory (IPC), Mini Nutritional Assessment (MNA-SF), and a biological risk screening based on the Child Development Assessment (EDI). Standardized z-scores and non-parametric tests were used for group comparisons and correlational analyses.ResultsChildren from exposed communities showed significantly greater executive functioning difficulties, particularly in behavioral, emotional, and cognitive regulation. BANETA scores revealed lower attention, more omission errors, and poorer writing and motor performance. Executive deficits were significantly associated with lower nutritional status and greater biological risk. Punitive parenting practices correlated with poorer regulation, while supportive parenting was linked to better academic performance.DiscussionThese findings support a multifactorial model where environmental, biological, and psychosocial stressors interact to adversely affect child development. Results underscore the need for integrated public health strategies, combining environmental remediation, educational support, nutrition, and caregiver-focused interventions in vulnerable communities.